Realist Criminology - Matthews, R. author. aut Link
XI, 179 p.
Keywords: This book challenges contemporary criminological thinking, providing a thorough critique of mainstream criminology, including both liberal criminology and administrative criminology. It sets a new agenda for theoretical and practical engagement, and for creating a more effective and just criminal justice system.